FLIGHT CREW FATIGUE AND THE EFFECT ON AIRLINE BUSINESS - MOHD RIZAL PALIL; LOKHMAN HAKIM OSMAN; MARA RIDHUAN CHE ABDUL RAHMAN; MOHD HELMI ALI; EZAD AZRAI JAMSARI; MAHATHIR AHMAD; NURUL AISHAH BINTI KHAIRUDDIN; NUR AAINA AQILAH BINTI JAMALUDDIN; IBNOR AZLI IBRAHIM; IDA SURIYA ISMAIL (Jurnal Bisnis dan Akuntansi, 2021)
The paper discusses previous studies on the effect of fatigue among flight crews and their effect on airline businesses. Fatigue is a major concern in flight operations as many reports were issued on this problem among flight crew. The long flight duration requires them to travel several time zones, which leads to fatigue. Furthermore, the change of time zones could also lead to the occurrence of jet lag and subsequently causes fatigue too. Fatigue can occur during and after the travelling period, and it takes a while to recover from it. This study aims to observe the effects of fatigue experienced by flight crew. The results show that fatigue causes many health problems such as an increase in cancer risk, depression, mental illness and miscarriage. Additionally, fatigue reduces one's work productivity as working in a tired state reduces work performance. Furthermore, fatigue also leads to other problems such as anger, anxiety, stress and job dissatisfaction. With the studies conducted on the issue of fatigue, airlines should take appropriate actions to minimise or solve the problem to ensure that fatigue problem will not affect flight crew performance and the airline business.